Direct evidence of histopathological impacts of wastewater discharge on resident Antarctic fish (Trematomus bernacchii) at Davis Station, East Antarctica - Corbett, PA; Catherine King; Stark, JS; Mondon, JA (2014)
During the 2009/2010 summer, a comprehensive environmental impact assessment (EIA) of the wastewater discharge at Davis Station, East Antarctica was completed. As part of this, histological alteration of gill and liver tissue in Antarctic Rock-cod ( Trematomus bernacchii ) from four sites along a spatial gradient from the wastewater outfall were assessed. All fish within 800 m of the outfall exhibited significant histological changes in both tissues. Common pathologies observed in fish closest to the outfall include proliferation of epithelial cells with associated secondary lamellar fusion in the gills and multifocal granulomata with inflammation and necrosis as well as cysts in the liver. Fish from sites >800 m from the outfall also exhibited alterations but to a lesser degree, with prevalence and severity decreasing with increasing distance from the outfall. This study highlights the value of histopathological investigations as part of EIAs and provides the first evidence of sub-lethal alteration associated with wastewater discharge in East Antarctica.